Mycamoeba gemmipara nov. gen., nov. sp., the First Cultured Member of the Environmental Dermamoebidae Clade LKM74 and its Unusual Life Cycle. (14th September 2016) - Blandenier, Quentin; Seppey, Christophe V. W.; Singer, David; Vlimant, Michèle; Simon, Anaële; Duckert, Clément; Lara, Enrique
Abstract: Since the first environmental DNA surveys, entire groups of sequences called "environmental clades" did not have any cultured representative. LKM74 is an amoebozoan clade affiliated to Dermamoebidae, whose presence is pervasively reported in soil and freshwater. We obtained an isolate from soil that we assigned to LKM74 by molecular phylogeny, close related to freshwater clones. We described Mycamoeba gemmipara based on observations made with light‐ and transmission electron microscopy. It is an extremely small amoeba with typical lingulate shape. Unlike other Dermamoebidae, it lacked ornamentation on its cell membrane, and condensed chromatin formed characteristic patterns in the nucleus. M. gemmipara displayed a unique life cycle: trophozoites formed walled coccoid stages which grew through successive buddings and developed into branched structures holding cysts. These structures, measuring hundreds of micrometres, are built as the exclusive product of osmotrophic feeding. To demonstrate that M. gemmipara is a genuine soil inhabitant, we screened its presence in an environmental soil DNA diversity survey performed on an experimental setup where pig cadavers were left to decompose in soils to follow changes in eukaryotic communities. Mycamoeba gemmipara was present in all samples, although related reads were uncommon underneath the cadaver.